Alexandre Lamfalussy and the monetary policy debates among central bankers during the Great Inflation - Ivo Maes; Piet Clement (National Bank of Belgium, 2018)
The 1970s were a turbulent period in postwar monetary history. This paper focuses on how central bankers at the Bank for International Settlements (BIS), especially Alexandre Lamfalussy, the BIS's Economic Adviser, responded to the Great Inflation. The breakdown of Bretton Woods forced central bankers to look for new monetary policy strategies as the exchange rate lost its central role. Lamfalussy, in his early years a Keynesian in favour of discretionary policies, moved to a "conservative Keynesian" position, acknowledging that a medium term orientation and the credibility of monetary policy were important to break inflationary expectations. However, Lamfalussy never moved to "monetarist" positions. Lamfalussy certainly acknowledged that monetary targets could reinforce the credibility and independence of monetary policy. However, he rejected mechanical rules. In essence he aimed for a middle position: rules applied with a pragmatic sense of discretion. In the early 1980s, with the rise of financial innovations, Lamfalussy would stress even more the limitations of monetary targeting. His focus turned increasingly to systemic financial stability risks, preparing the ground for the macroprudential approach of the BIS. In Lamfalussy's view, central banking remained an art, not a science.
Keywords: B22; E58; F44; 330; Great Inflation; monetary policy; central banking; Alexandre Lamfalussy; BIS